Trauma vicariante e burnout em profissionais de saúde que atendem mulheres e crianças vítimas de violência sexual - Antonio, Daiana Oliveira Costa (2024)
Health professionals providing assistance to individuals who are victims of sexual violence face specific challenges that can lead to the development of stress, burnout, and vicarious trauma. Exposure to reports of violence, suffering, and trauma can have a significant impact on physical, psychological, and social health. This study aimed to investigate the presence of vicarious trauma and burnout among health professionals who serve women and children victims of sexual violence in two institutions in the state of São Paulo. To achieve this goal, a mixed-method research was conducted, involving 27 health professionals including social workers, nurses, physicians, and psychologists. Quantitative data were collected using the ProQOL-IV BR, ISSL-R, EBBurn, and QUESI instruments to assess stress, burnout, vicarious trauma, and the presence of early traumas. Qualitative information was gathered through semi-structured interviews, from which six thematic categories were derived: professional demeanor, impact on personal life, triggered emotions and feelings, coping strategies, institutional solutions and measures, and suffering and satisfaction. The quantitative results indicated a high level of compassion satisfaction and a low level of vicarious trauma and burnout. However, the qualitative findings, despite also indicating high levels of compassion satisfaction, showed signs of stress and emotional distress, along with symptoms consistent with burnout development. The investigation emphasized the importance of compassion satisfaction for professionals to remain in their field, but it also revealed that professionals feel exhausted and neglected. Therefore, this is a frustrating, difficult, heavy, and demanding job, despite being rewarding and fulfilling, which brings about changes in the professionals' worldview and personal life. The results point to the need for further studies on the topic to ensure promotion and prevention of the healthcare professionals' health who work with trauma victims